L’implicite comme moyen de persuasion : une approche quantitative - Edoardo Lombardi Vallauri (Corela)
Among linguistic implicits, implicatures leave implicit part of the content expressed by utterances, while presuppositions and topicalizations conceal the speaker’s responsibility for the introduction of that content. They both effect what Givón (1982) calls the unchallengeability of some information, i.e. its being difficult to critically evaluate and reject on the part of the addressee. This function of implicits extensively characterizes persuasive texts. The paper aims at quantifying the implicitation of contents and speaker responsibility in some political and commercial advertisements, by means of a system of indexes attributed to the mentioned categories (Lombardi Vallauri & Masia 2014). This proceeding is proposed as an example of how linguistic analysis can contribute to the improvement of fairness in commercial advertising and in political propaganda, which is at the basis of democratic cohabitation.